Management of endo-perio lesion in a tooth with an unfavorable prognosis : a clinical case report with an 18-month follow-up = Tratamiento de una lesión endo-perio-perio en un diente de pronóstico desfavorable:informe de un caso clínico con seguimiento durante 18 meses - Sandini Trentin, Micheline; Gomes Dallepiane, Felipe; Serraglio Figueiredo, Paola; Becker, Ana Luiza; Leocovick, Síndel (2024)
The aim of this case study is to report a successful clinical case of an endo-perio lesion in a tooth with an initially unfavorable prognosis, followed up for 18 months. A male patient, public servant, non-smoker, without a history of diabetes, and married sought dental treatment in 1995 due to periodontal problems. He was then 40 years old and diagnosed with moderate to advanced periodontal disease. The initial treatment consisted of supra and subgingival scaling, followed by the extraction of teeth indicated for removal. After discharge, the patient adhered to a preventive periodic maintenance (PPM) program to control periodontal disease recurrence. In 2021, tooth 43 showed an unfavorable endo-perio lesion during a routine check-up. Despite treatment options, the patient opted for conservative treatment with endodontic and periodontal procedures. Simultaneously, PPM sessions were performed. The patient was monitored every six months, showing regression of periodontal pockets and significant improvement after 18 months. This case highlights the importance of patient adherence to PPM, demonstrating that a conservative approach and proper maintenance can lead to positive clinical outcomes even in cases with an initially unfavorable prognosis.
El objetivo de este estudio de caso es informar de un caso clínico exitoso de una lesión endo-perio en un diente con un pronóstico inicialmente desfavorable, seguido durante 18 meses. Un paciente varón, funcionario público, no fumador, sin antecedentes de diabetes y casado buscó tratamiento odontológico en 1995 debido a problemas periodontales. Tenía entonces 40 años y se le diagnosticó enfermedad periodontal de moderada a avanzada. El tratamiento inicial consistió en un raspado supra y subgingival, seguido de la extracción de los dientes cuya extracción estaba indicada. Tras el alta, el paciente siguió un programa de mantenimiento periódico preventivo (MPP) para controlar la recidiva de la enfermedad periodontal. En 2021, el diente 43 mostró una lesión endoperio desfavorable durante una revisión rutinaria. A pesar de las opciones de tratamiento, el paciente optó por un tratamiento conservador con procedimientos endodónticos y periodontales. Simultáneamente, se realizaron sesiones de MPP. Se realizó un seguimiento semestral de la paciente, que mostró una regresión de las bolsas periodontales y una mejora significativa al cabo de 18 meses. Este caso pone de relieve la importancia de la adherencia del paciente al MPP, demostrando que un enfoque conservador y un mantenimiento adecuado pueden conducir a resultados clínicos positivos incluso en casos con un pronóstico inicialmente desfavorable.
En revista Odóvtos, vol. 26, no.3 (setiembre-diciembre 2024)
Descripción basada en el contenido visto el 07 de febrero, 2025
También disponible en formato HTML y EPUB